The Return of Religious Antisemitism? - Jikeli, Gunther (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The most violent American and European anti-Semites in the 21st century, including not only Jihadists but also white (and black) supremacist terrorist, made some reference to religion in their hatred of Jews. This is surprising. Religious antisemitism is often seen as a relic of the past. It is more associated with pre-modern societies where the role of religion was central to social and political order. However, at the end of the 19th century, animosity against Judaism gave way to nationalistic and racist motives. People, such as Wilhelm Marr, called themselves anti-Semites to distinguish themselves from those who despised Jews for religious reasons. Since then, antisemitism has gone through many mutations. However, today, it is not only the actions of extremely violent anti-Semites who might be an indication that religious antisemitism has come back in new forms. Some churches have been accused of disseminating antisemitic arguments related to ideas of replacement theology in modernized forms and applied to the Jewish State. Others, from the populist nationalist right, seem to use Christianity as an identity marker and thus exclude Jews (and Muslims) from the nation. Do religious motifs play a significant role in the resurgence of antisemitism in the 21st century?